OP54 Exploring Socioeconomic Inequalities in Coronary Heart Disease Prevention. (10th September 2013) - Ahmed, R; O'Flaherty, M; Anwar, E; Hawkins, N; Wilkinson, E; Lucy, J; Capewell, S
Abstract : Background: Between 2000 and 2007, coronary heart disease (CHD) mortality rates in England plummeted by one third. An important part of this substantial CHD mortality decline was achieved through reductions in major cardiovascular risk factors (primary prevention). However, the relative contributions from medications and from population-wide changes remains unclear, particularly the effects on health inequalities. Methods: Using a previously validated policy model, the fall in CHD mortality in England was analysed. The contributions from risk factor declines in asymptomatic individuals through medications and through population-wide changes were quantified. Data were stratified using the Index of Multiple Deprivation (IMD). Model outputs were quantified as deaths prevented or postponed (DPPs). Results: Between 2000 and 2007, approximately 21, 900 fewer CHD deaths were attributable to risk factor declines in systolic blood pressure and cholesterol in the English population. Some 7, 100 of these 21, 900 fewer deaths (DPPs) were attributed to medications (32%) and approximately 14, 800 DPPs were attributed to secular changes in asymptomatic individuals (68%). Substantial declines in systolic blood pressure were responsible for approximately 14, 300 fewer deaths. This comprised approximately 12, 500 DPPs attributable to population-wide changes and some 1, 800 DPPs attributable to hypertension medications. The hypertension medications resulted in approximately 350 fewer deaths in the most affluent quintile compared with 270 DPP in the most deprived. In contrast, the population-wide (secular) falls in blood pressure resulted in approximately 2400 fewer deaths in the most deprived quintile compared with only 1900 DPPs in the most affluent. Cholesterol falls resulted in approximately 7, 700 fewer deaths. This comprised some 5, 300 fewer deaths attributable to statin medications and approximately 2, 400 fewer deaths attributable to population-wide changes (mostly diet). Statin medications prevented more deaths in the most affluent quintile (1050 DPPs) compared with the most deprived (770 DPPs). Population-wide changes in cholesterol prevented substantially more deaths in the most deprived quintile (820 DPPs) compared with the most affluent (260 DPPs). Conclusion: Population-based declines in blood pressure and cholesterol resulted in much greater reductions in CHD deaths than did primary prevention medications. Mortality falls were greatest in the most deprived quintiles, mainly reflecting their bigger initial burden of disease. Future CHD prevention policies should prioritise healthier diets ahead of medications.